Penanaman Nilai Islami Untuk Mencegah Pergaulan Bebas Pada Raja - Iklima Sophia Rohim; Yulfa, Rahmi (Sekolah Tinggi Ilmu Tarbiyah Insan Kamil Bogor, 2024)
Free association for teenagers is a serious and increasingly concerning social problem. Most teenagers now prefer to follow current fashion trends, such as Western dress styles, behavior that deviates from prevailing norms, smoking, drinking alcohol, using illegal drugs, free sex, violence, etc. The main objective of this study is to provide information and understanding to the public, especially teenagers about this phenomenon. The research approach applied is a qualitative approach, with the type of literature study. The subjects in this study are various data obtained from literature studies. The data collection technique applied to literature studies. The data analysis technique applied descriptive analysis. The study results show that free association in teenagers is due to internal and external factors. Free association in teenagers has an impact on physical and psychological damage to teenagers. Prevention of free association in teenagers is a shared responsibility of various parties, from family, school, community, and government. Instilling Islamic values is one of the most effective efforts to prevent free association in teenagers. By instilling strong Islamic values, it is hoped that teenagers can avoid free association and become a generation with character and noble morals.